Peer mentoring for individuals with an eating disorder: a qualitative evaluation of a pilot program - Freya Hanly; Benjamin Torrens-Witherow; Narelle Warren; David Castle; Andrea Phillipou; Jennifer Beveridge; Zoe Jenkins; Richard Newton; Leah Brennan (Journal of Eating Disorders, 2020)
Abstract Background After receiving intensive medical treatment; individuals with eating disorders often require ongoing care to maintain their recovery, build social networks, and reduce risk of relapse. Methods To address this important transition period, a six-month peer mentoring program was developed and piloted in Melbourne, Australia. Twelve adults with a past history of an eating disorder (mentors) were paired with 14 individuals with a current eating disorder (mentees). Pairs met for thirteen mentoring sessions in community settings. Throughout the program mentees and mentors completed reflective questions online. Upon completion of the program, qualitative interviews were conducted. Both online reflections and interviews explored themes relating to perceived benefits and challenges of participation in the peer mentoring program, and the differences between mentoring and traditional treatment. Results Thematic analysis identified several benefits for mentees; including hope, reconnection with others, and re-engaging with the world. The majority of mentees described their mentor as uniquely supportive due to their past experience of an eating disorder. Mentors reported experiencing benefits such as increased connection with self and others, and indicated that the experience helped them positively reframe their past experience of an eating disorder. Ending the relationship at the completion of the program was a significant challenge for both groups, and managing boundaries was deemed a main challenge by mentors. Conclusions Overall, results indicated that this mode of informal support may be worthy of further investigation as an adjunct to clinical treatment programs for this population. Trial registration Australian and New Zealand Clinical Trials registration number - ACTRN12617001412325 - Date of registration – 05/10/2017 (Retrospectively registered)